NOMENKLATUR PEMIKIRAN HUKUM SYAIKH ARSYAD AL-BANJARIY - Moh. Fahimul Fuad (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
The being of Islamic igures in Indonesia in past becomes important in the history of Islamic world. There is main chain which is connecting among Indonesian Islamic igure and others especially in Middle East. This main chain particularly to the relation of geneology science of Middle East, especially in Makkah-Madinah, until becomes igure who has a reputation and network level-world. One of the Islamic Nusantara’s igures who has a important role in the religious living in this country is Muhammad Arsyad al-Banjari. From main chain side of knowledge, he belongs with ‘the graduate of Middle East.’ In this point, it becomes important to go along how the construct of Arsyad Al-Banjari’s thought is, as in his work (kitab). This investigation of course will engage ‘the biographic side’ from the igure, including geneology of knowledge and also science posture which is taken when it is closed to the reality of the society. The thought of al-Banjari about marital law, especially in his kitab, annikah. This kitab speci ically examines the marriage with the systematic from marital law, essential principles, till the break of marriage including the detail in each contain. In that kitab, the law that al-Banjari offers, ‘almost’ all of them adopt from Fiqh Sya i’iyyah.